Iron and Vitamin A Intake with the Incidence of Anemia in Adolescent Girls - Prihantika, Devanda Amelia; Hidayati, Listyani; Puspitasari, Dyah Intan (Sarana Ilmu Indonesia (salnesia), 2025)
Iron is an essential micronutrient, particularly for blood formation and hemoglobin synthesis. Vitamin A contributes by mobilizing iron reserves in the body, thereby supporting hemoglobin production. This study aimed to examine the association between iron and vitamin A intake and the incidence of anemia among adolescent girls in Surakarta. A cross-sectional design with multistage random sampling was employed, involving 199 female students who met the inclusion and exclusion criteria. Hemoglobin levels were assessed using the cyanmethemoglobin method, while dietary intake of iron and vitamin A was measured through the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) to evaluate dietary habits. Statistical analysis revealed a significant association between iron intake and anemia (p-value= <0,001), whereas vitamin A intake showed no significant relationship (p-value= 0,132). The findings indicate that inadequate iron intake contributes to anemia in adolescent girls. Further research with larger sample sizes and longitudinal approaches is strongly recommended to elucidate the role of vitamin A and to inform more effective anemia prevention strategies.